Characterization of macroscopic measures in the articular disc of the temporomandibular joint in different age groups: A morphological and statistical analysis in fresh temporomandibular joints (Research, Society and Development, 2024)
Perforation of the temporomandibular joint disc is a condition that can lead to severe pain and functional impairments. This project aims to study the changes present in the articular disc during human aging, considering its macroscopic dimensions, perforation rates, age, and sex. Using an observational study, 16 temporomandibular joints were collected from 08 lifeless bodies by bicoronal post-auricular access. Articular discs were analyzed and recorded via photography. A digital caliper was used to analyze the dimensions of thickness and depth. Sex, age, laterality, thickness in millimeters, extension from medial to distal, and presence of perforation were observed. Pearson’s and ANOVA tests were performed. Results show a mean age of 69.75 years (44-87 years, ± 12.5), mean thickness of 2.99 mm (2.07-4.23 mm, ± 0.628,) and mean side-to-side dimension of 21.77 mm (11.40-26.38 mm, ± 3.785) and only one piece with disc perforation present (6.25%) – other results suggest at a moderate correlation between variables. The results of this project are in harmony with other studies in terms of variability in the dimensions of the articular disc related to disc perforation. Given the context, it is suggested that other factors to be investigated in subsequent studies, in addition to those studied in this project, may individually influence the presence or absence of perforation.